THE EFFECTIVENESS OF USING TIKTOK TO IMPROVE EFL LEARNERS’ SPEAKING ABILITY - Diko Putri, Syifa Mutiara (MIMESIS, 2022)
People are drawn to the internet as technology progresses. During the COVID-19 pandemic, technology has become a requirement in the education sector. Therefore, the researchers want to find the effectiveness of TikTok in improving EFL learners' speaking ability. The subject of this paper was 20 from the English Educational Study Program at Tidar University. This study used the qualitative research method. Based on the researchers' study with 20 students from the English Educational Study Program, the researcher concludes that the TikTok application improved students' speaking skills well. In addition, students' sentiments toward using TikTok in language learning were favorable.